Design, Construction, and Calibration of a Low-Cost Portable Dip-Coating Machine for Laboratory Applications - Abdulrahman, M. A.; Sumaila, M.; Dauda, M.; Abubakre, O. K. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2026)
Precise control of withdrawal speed and immersion height is essential for achieving uniform coatings and ensuring process reproducibility in dip-coating techniques. Commercial dip-coating systems capable of such control are often costly, limiting their accessibility to emerging and resource-constrained laboratories. This work reports the design, fabrication, and performance evaluation of a simple, portable, and low-cost automated dip-coating system intended for laboratory-scale surface coating applications. The system integrates mechanical and electronic subsystems, with the motor–lead screw assembly selected based on fundamental mechanical design principles. Automated control of immersion and withdrawal processes was implemented using an Arduino Uno microcontroller. Calibration of immersion height and withdrawal speed was performed using a Vernier caliper and a tachometer, respectively. The assembled system demonstrated reliable operation within an immersion height range of 70–220 mm and a withdrawal speed range of 0.5–7 mm s⁻¹, with maximum deviations of 0.75% and 2.0%, respectively. The total material cost of the dip coater was approximately USD 97. The adjustable immersion height feature enables reduced operational time and improved energy efficiency during coating processes. Owing to its accuracy, reproducibility, and affordability, the developed system offers a practical alternative to commercial dip coaters for thin-film deposition and surface protection research.